Disorder of the structure and vascularization of the villi of placenta at the preeclampsia - A I Shchegolev; U N Tumanova; V M Lyapin (IP Berlin A.V., 2018)
Preeclampsia is considered one of the most serious diseases of pregnancy and cause serious complications in the mother and fetus. The emergence and development of preeclampsia is due to the violation of placental processes. The literature data on microscopic changes in the structure and vascularization of placental villi in preeclampsia are analyzed. Violations of the structure and vascularization of villi placenta in preeclampsia are noted. This, undoubtedly, indicates their role in the development and progression of this complication of pregnancy. Lower values of the extent, surface area and volume of villi, as well as their degree of vascularization, are registered in observations of early preeclampsia. The ambiguity of the data of morphometric and stereo metric indices of villi, which are available in the literature, is most likely due to the investigation of placentas at various stages of gestation and with varying degrees of severity of preeclampsia. An important link in the pathogenesis of preeclampsia and a factor in violations of the villi development is a change in the levels of pro-angiogenic and anti-angiogenic factors, mainly the vascular endothelial growth factor and its receptors. For a complete analysis of the causes and characteristics of preeclampsia is necessary to conduct a comprehensive macroscopic and microscopic examination of the placenta.